The Basic Writings of Josiah Royce, Volume I Culture, Philosophy, and Religion - McDermott, John J. (American Philosophy, 2005)
Now back in print, and in paperback, these two classic volumes illustrate the scope and quality of Royce's thought, providing the most comprehensive selection of his writings currently available. They offer a detailed presentation of the viable relationship Royce forged between the local experience of community and the demands of a philosophical and scientific vision of the human situation. The selections reprinted here are basic to any understanding of Royce's thought and its pressing relevance to contemporary cultural, moral, and religious issues.